Modeling of the effect of ionomer volume fraction on water management for proton exchange membrane fuel cell. (February 2019) - He, Pu; Chen, Li; Mu, Yu-Tong; Tao, Wen-Quan
Abstract: Proton exchange membrane fuel cell (PEMFC) has been recognized as the most promising energy conversion device due to its outstanding merits, such as high energy efficiency, low pollution, low operating temperature and low noise. Due to the complicated process of water production and transportation in porous media, the water concentration can affect the distribution of species and ionic conductivity, thus, the water management has been regarded as one of the most critical issues for PEMFC. In this paper, a three dimensional multiphase non-isothermal model for the PEMFC performance prediction has been developed to study the effect of ionomer volume fraction on the performance of PEMFC. The numerical results show that the ionomer volume fraction of catalyst layer has an appreciable effect on the performance of PEMFC and water distribution in porous electrodes, the higher ionomer volume fraction in catalyst layer can be helpful to avoid the flooding problem in porous electrodes.